2021
DOI: 10.34172/mejdd.2021.205
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Aerobic Exercise and Diaphragmatic Breathing on Lower Esophageal Sphincter Pressure and Quality of Life in Patients with Reflux: A Comparative Study

Abstract: BACKGROUND Gastroesophageal reflux disease (GERD) is a worldwide disorder with an increasing prevalence. The quality of life (QOL) of the patients may be influenced by reflux disease. Diaphragmatic breathing (DB), as well as aerobic exercise (AE), may improve the symptoms of reflux disease, although it remains a controversial issue. The aim of this study was to compare the effects of AE and DB on QOL and lower esophageal sphincter (LES) pressure of patients with moderate to severe reflux. METHODS This was a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(30 reference statements)
2
3
0
Order By: Relevance
“…According to Bundy et al (2018), adult blood pressure increases with age, especially when entering old age, blood pressure increases due to a decrease in the elasticity of blood vessels. This study is in accordance with research conducted by Ahmadi et al (2021) which states that most of the incidence of hypertension increases rapidly at the age of 50 years and over with a prevalence of 69.7%.…”
Section: Discussionsupporting
confidence: 92%
“…According to Bundy et al (2018), adult blood pressure increases with age, especially when entering old age, blood pressure increases due to a decrease in the elasticity of blood vessels. This study is in accordance with research conducted by Ahmadi et al (2021) which states that most of the incidence of hypertension increases rapidly at the age of 50 years and over with a prevalence of 69.7%.…”
Section: Discussionsupporting
confidence: 92%
“…This could be related to abdominal breathing that improved their exercise capacity, respiratory function, and affects positively GERD clinical symptoms. 27 This study confirmed a significant inverse correlation between patient breathing exercise compliance and GERD symptoms severity, frequencies, and antacid consumption at two-and four-month post-intervention. This finding was congruent with Qiu et al, who reported that there was a negative correlation between breathing exercises and GERD symptoms, and acid suppression usage whereas patients who performed breathing exercises had lower mean scores of GERD symptoms severity and frequencies.…”
Section: Discussionsupporting
confidence: 77%
“…This could be related to abdominal breathing that improved their exercise capacity, respiratory function, and affects positively GERD clinical symptoms. 27…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that breathing exercises may improve LES fibre tension, reducing the frequency of one-time oesophageal relaxation and increasing the rate of gastric emptying 23 . Moreover, as shown by Amhadi et al, standardised diaphragmatic breathing significantly improved quality of life and was able to induce significant change in LES pressure when evaluated by oesophageal manometry 24 . Preliminary data published by Moffa et al 25 emphasised how a specific inspiratory muscle training technique could be useful, alone or in association with diet/PPI, in significantly improving GERD symptoms, RSI and laryngeal endoscopy score after 4 weeks of treatment.…”
Section: Discussionmentioning
confidence: 76%